ALIENASI MANUSIA MODERN KRITIK MODERNITAS DALAM PEMIKIRAN ERICH FROMM - Nufi Ainun Nadhiroh (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2015)
Alienation is a term that has been used by many thinkers in the past, including Hegel and Karl Marx. Every thinker gives its meaning differently. Hegel supposed that this alienation's discussion is important in relation  to the emerging  of consciousness or the feeling towards the otherness. Karl Marx discussed about alienation when he concerned about the fate of labors that had been exploited by the bourgeoisies. It is explained in this article,  Fromm has been influenced by both thinkers, but he also criticized them that their applications to solve human alienation conditions always find the deadlock because  they simply focused to single aspect only. Fromm proposed  an idea that to heal the ill modem society; they should  perform the change not only in single aspect oflife but also the change  in all aspects simultaneously such as industry and political organization,  spiritual, philosophical orientation, human character structure and cultural activity. Fromm assumed that to create healthy society, it starts from the self awareness. This is identical to human nature as the aware and foremost creature.